2009
DOI: 10.1111/j.1467-8276.2008.01175.x
|View full text |Cite
|
Sign up to set email alerts
|

Food Values

Abstract: Because of the potential malleability of stated and revealed preferences for new food technologies and attributes, this research sought to determine consumers' food value systems by utilizing recent advances in best-worst scaling. Based on previous literature related to human values and food preferences, a list of eleven food values was compiled. Results reveal that on average the values of safety, nutrition, taste, and price were among the most important to consumers, whereas the values of fairness, tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
609
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 547 publications
(641 citation statements)
references
References 34 publications
28
609
2
2
Order By: Relevance
“…Previous studies have employed similar methodology to that selected for this analysis (Grunert and Juhl, 1995;Cicia et al, 2002;Makatouni, 2002;Zanoli and Naspetti, 2002;Baker et al, 2004;Padel and Foster, 2005). And another set of researchers has already demonstrated that the choice of organic foods is influenced by an emotional response that varies with the individual's personal values (Grunert and Juhl, 1995;Barreiro et al, 2002;Makatouni, 2002;Fraj et al, 2004;Hoogland et al, 2005;Verhoef, 2005;Kihlbert and Risvik, 2007;Lusk and Briggeman, 2009). One of the main differentiating features of our study, nevertheless, is the use of a method that enables us to quantify and statistically analyse differences in the cognitive structures of regu-lar and occasional purchasers of organic foods.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies have employed similar methodology to that selected for this analysis (Grunert and Juhl, 1995;Cicia et al, 2002;Makatouni, 2002;Zanoli and Naspetti, 2002;Baker et al, 2004;Padel and Foster, 2005). And another set of researchers has already demonstrated that the choice of organic foods is influenced by an emotional response that varies with the individual's personal values (Grunert and Juhl, 1995;Barreiro et al, 2002;Makatouni, 2002;Fraj et al, 2004;Hoogland et al, 2005;Verhoef, 2005;Kihlbert and Risvik, 2007;Lusk and Briggeman, 2009). One of the main differentiating features of our study, nevertheless, is the use of a method that enables us to quantify and statistically analyse differences in the cognitive structures of regu-lar and occasional purchasers of organic foods.…”
Section: Introductionmentioning
confidence: 87%
“…Numerous authors have shown that the key factor governing organic food choice is to found in a series of concrete product attributes: a better taste or better organoleptic properties in general (Wier and Calverley, 2002;Magnusson et al, 2003;Bähr et al, 2004;Baker et al, 2004;Chryssohoidis and Krystallis, 2005;Arvola et al, 2008;Lusk and Briggeman, 2009); price as a product quality cue (Ritcher et al, 2000;Cicia et al, 2002;Wier and Calverley, 2002); geographic origin, local organic produce being preferred (Wier et al, 2008;Lusk and Briggeman, 2009) and product appearance (Zanoli and Naspetti, 2002; among others).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Although some research studies have focused on the importance of adequate nutrition information, the focus of these studies has been the retail sector and knowledge about consumer information needs in workplace canteens is lacking (Carbone and Zoellner 2012). Furthermore, consumer interests go beyond the search for nutritional information with curiosity for information on other quality attributes and origins of food (Lusk and Briggeman 2009). …”
Section: Luhmann (2000)mentioning
confidence: 99%
“…These K(K − 1) options refer to all possible best-worst pairs of attribute-levels given a profile, or job in our application. In the context of the object case BWS (Flynn, 2010b), which is like the single profile case BWS with only one possible level per attribute, Lusk and Briggeman (2009) explicitly describe it as a form of the latent dependent variable model.…”
Section: Models For Single Profile Case Datamentioning
confidence: 99%
“…Marley and Louviere (2005) and Marley et al (2008) develop alternative models to analyse the resulting data. In particular, they prove a number of choice theoretical properties of the maximum difference logit (max-diff) model, that has since been the workhorse model in empirical studies (Flynn et al, 2007;Lusk and Briggeman, 2009;Lusk and Natalie, 2009;Potoglou et al, 2011;Marti, 2012).…”
Section: Models For Single Profile Case Datamentioning
confidence: 99%